2019
DOI: 10.3233/jpd-191798
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Speech Change After Subthalamic Nucleus Deep Brain Stimulation in Parkinson’s Disease Patients: A 2-Year Prospective Study

Abstract: Background: Speech disorders are among the most common adverse effects after subthalamic nucleus deep brain stimulation (STN-DBS) in Parkinson's disease (PD) patients. However, longitudinal speech changes after STN-DBS are not fully understood. Objective: We performed a two-year prospective study on PD patients who underwent STN-DBS and analyzed changes in speech function to clarify factors predicting for speech deterioration. Methods: Twenty-five PD patients were assessed before and up to two years after STN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
3
21
0
2
Order By: Relevance
“…Anyway, these results contrast strongly with the results of speech performance in patients with advanced PD. At these later stages, speech intelligibility assessments 36,37 and other subjective/perceptual measures 5,38 usually show an undisputable deterioration over such a long observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, these results contrast strongly with the results of speech performance in patients with advanced PD. At these later stages, speech intelligibility assessments 36,37 and other subjective/perceptual measures 5,38 usually show an undisputable deterioration over such a long observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, surgical interventions have also caused an academic debate. For example, deep brain stimulation of the subthalamic nucleus has been proven to be a safe and long-term effective treatment for limb motor symptoms in patients with advanced PD, but the effect on speech remains unclear [45][46][47][48]. Although many studies have demonstrated improvements in some voice characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nicht durch die THS beeinflussen lässt sich eine orthostatische Dysregulation [9], während sich andere, nicht motorische Symptome wie Blasenentleerungsstörungen [10] oder übermäßiges Schwitzen und Schlafstörungen [11] bessern können. Bezüglich des Sprechens und der Sprache können Patient*innen, deren Dysarthrophonie an die Off-Phasen gebunden ist, mit einer Verringerung dieser Problematik durch die THS rechnen [12], [13].…”
Section: Vorsichtunclassified
“…Off-gebundene Stimm-und Sprechstörungen können sich unter einer THS stimulationsabhängig auch verbessern [12,13,19]. Die Wortflüssigkeit kann sich postoperativ verschlechtern.…”
Section: Auswirkungen Der Ths Auf Sprechen Und Spracheunclassified